Reappraising verbal language in audiovisual translation: From description to application - Pavesi, Maria (Journal of Audiovisual Translation, 2018)
Focussing on the verbal code alone in audiovisual translation research is often criticised as it supposedly disregards the semiotic and cultural complexity of the audiovisual text. This article by contrast argues for the relevance of an in-depth analysis of the linguistic component of the multimodal complex. First, the article presents a model of key dimensions necessary to account for the space occupied by the language of dubbing, while placing it within a wider sociolinguistic context. Three pairs of dimensions are proposed: naturalness and register specificity, target language orientation and source language interference, and routinisation and creativity. Second, the article argues that translation for dubbing can be applied as a heuristic device to explore the translation of casual conversation. By analysing the rendering of a typical structure of conversational English in dubbed Italian, an illustration is provided of systematic cross-linguistic correspondences that potentially extend to spontaneous speech. Further sociolinguistic, diachronic and cross-cultural investigations are suggested as a way to push research into the language of dubbing forward.